2017
DOI: 10.3390/math5040079
|View full text |Cite
|
Sign up to set email alerts
|

Convertible Subspaces of Hessenberg-Type Matrices

Abstract: Abstract:We describe subspaces of generalized Hessenberg matrices where the determinant is convertible into the permanent by affixing ± signs. An explicit characterization of convertible Hessenberg-type matrices is presented. We conclude that convertible matrices with the maximum number of nonzero entries can be reduced to a basic set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…To prove [5,Conjecture 8] first da Fonseca in [8] showed that the permanent of the matrix T n (−1, 2x, 1), with respect to the fact, that the permanent of a square matrix equals the sum of the weights of all cycle-covers of its underlying directed graph. Then, he used a result on convertible matrices from his paper [10] (some generalizations can be found in [11]) to show that the permanent of matrix T (k) n (−1, 2x, 1) is equal to the determinant of the matrix T…”
Section: Introductionmentioning
confidence: 99%
“…To prove [5,Conjecture 8] first da Fonseca in [8] showed that the permanent of the matrix T n (−1, 2x, 1), with respect to the fact, that the permanent of a square matrix equals the sum of the weights of all cycle-covers of its underlying directed graph. Then, he used a result on convertible matrices from his paper [10] (some generalizations can be found in [11]) to show that the permanent of matrix T (k) n (−1, 2x, 1) is equal to the determinant of the matrix T…”
Section: Introductionmentioning
confidence: 99%